Induction and maintenance of remission with mycophenolate mofetil in ANCA-associated vasculitis: a systematic review and meta-analysis - Berti, Alvise; Alsawas, Mouaz; Jawaid, Tabinda; Prokop, Larry J; Lee, Jiwon M; Jeong, Gwang Hun; Quintana, Luis F; Moiseev, Sergey; Vaglio, Augusto; Tesar, Vladimir; Geetha, Duvuru; Shin, Jae I L; et al. (Nephrology, dialysis, transplantation, 2022)
BACKGROUND: Uncertainties exist about the use of mycophenolate mofetil (MMF) in anti-neutrophil cytoplasmatic antibody (ANCA)-associated vasculitis (AAV), particularly for remission maintenance. METHODS: Systematic review and meta-analysis of phase II and III trials assessing the use of MMF in AAV, granulomatosis with polyangiitis and microscopic polyangiitis (MPA). A comprehensive search of several databases (Medline, EMBASE, Cochrane, Web of Science, Scopus) from inception to 5 May 2020 has been conducted. Trial data were extracted to estimate odds ratios (ORs) and estimates (ES) for MMF efficacy (remission-induction and maintenance). Severe adverse effects (SAEs) were collected. RESULTS: From 565 articles captured, 10 met the predefined criteria, 5 phase II and 5 III trials; 4 assessed remission-induction, 3 remission maintenance and 3 both. The pooled OR for remission-induction at 6 months was 1.06 (95% confidence interval 0.74, 1.52), with no significant difference by subgroup meta-analysis of trials stratified by different study-level features (i.e. kidney disease, MPA, myeloperoxidase-ANCA positivity, newly diagnosed disease) (P > 0.05). The overall ES for remission maintenance at the end of follow-up ranged between 51% and 91% (I2 = 74.8%). Subgroup meta-analysis identified kidney involvement as a possible source of heterogeneity, yielding a significantly higher rate of sustained remission in trials enrolling only patients with kidney involvement (92%, 76-100%) versus those enrolling patients with and without kidney involvement (56%, 45-66%). Results were similar in multiple sensitivity analyses. During follow-up, the frequency of SAEs in MMF-based treatment arms was 31.8%. CONCLUSIONS: In AAV, MMF use was significantly associated with higher sustained remission rates in trials enrolling only patients with kidney involvement. These findings might influence clinical practice.
Keywords: MMF; Peroxidase; ANCA-asociované vaskulitidy; Humans; microscopic polyangiitis; mycophenolate mofetil; protilátky proti cytoplazmě neutrofilů; Mycophenolic Acid; peroxidasa; lidé; imunosupresiva; granulomatosis with polyangiitis; indukce remise; Immunosuppressive Agents; mikroskopická polyangiitida; Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis; Antibodies, Antineutrophil Cytoplasmic; Microscopic Polyangiitis; Remission Induction; kyselina mykofenolová; ANCA-associated vasculitis